Evaluation of Collaborative Tourism Management during a Pandemic - Dorthea Renyaan (Jurnal Manajemen Pelayanan Publik, 2023)
This study aims to evaluate collaboration-based tourism management during a pandemic. The design used in this study is descriptive qualitative with a literature study approach. The survey results show that collaboration in tourism management in Indonesia during the pandemic refers to three dominant research themes: accelerated recovery based on cooperation between institutions, a partnership between the government and tourism actors, and collaboration in developing tourism villages. However, further study must explore the concern for capacity building and organizational learning in rural communities. So the results of this study require further research that reviews more capacity building and organizational learning to increase village community collaboration in the tourism sector.